2000
DOI: 10.1210/endo.141.11.7765
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Deficiency, Obesity, and Skeletal Abnormalities in Follicle-Stimulating Hormone Receptor Knockout (FORKO) Female Mice**This investigation was supported in part by the Canadian Institutes of Health Research.

Abstract: Targeted disruption of the receptor for glycoprotein hormone, FSH (FSH-R) causes a gene dose-related endocrine and gametogenic abnormality in female mice. The resulting FSH-R knockout (FORKO) mutants have disordered estrous cycles, ovulatory defects, and atrophic uterus. The heterozygous animals that initially show reduced fertility undergo early reproductive senescence and stop breeding altogether. Lack of FSH-R signaling in females causes severe ovarian underdevelopment producing chronic estrogen deficiency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(22 citation statements)
references
References 38 publications
4
16
0
Order By: Relevance
“…This clinical phenotype has often been documented in rodents post-ovariectomy, as well as in chronic hypoestrogenemic models, such as in female Erα −/− , aromatase −/− and Fshr −/− mice 4, 1618 , although in our hands, female Fshr −/− mice are not obese. While in female mice, genetic Fshr deficiency does not seem to protect against the pro-adiposity effects of severe chronic hypoestrogenemia, we questioned whether acute suppression of Fsh by an Fsh Ab can, through parallel mechanisms, not only attenuate bone loss 6 , but also reduce body fat and improve energy homeostasis.…”
Section: Fsh Ab Reduces Adiposity In Ovariectomized Micesupporting
confidence: 48%
“…This clinical phenotype has often been documented in rodents post-ovariectomy, as well as in chronic hypoestrogenemic models, such as in female Erα −/− , aromatase −/− and Fshr −/− mice 4, 1618 , although in our hands, female Fshr −/− mice are not obese. While in female mice, genetic Fshr deficiency does not seem to protect against the pro-adiposity effects of severe chronic hypoestrogenemia, we questioned whether acute suppression of Fsh by an Fsh Ab can, through parallel mechanisms, not only attenuate bone loss 6 , but also reduce body fat and improve energy homeostasis.…”
Section: Fsh Ab Reduces Adiposity In Ovariectomized Micesupporting
confidence: 48%
“…Currently, mouse models of female reproductive aging are divided into two categories: genetic mutation animal models, such as the follitropin receptor knockout animal model [4, 5] and the dioxin/aryl hydrocarbon receptor knockout animal model [6, 7]; and poison damage models, such as the 4-vinylcyclohexene diepoxide-induced female reproductive aging model [8, 9] and the D-galactose-induced female reproductive aging model [10-12]. Although these animal models show an increase in follicular consumption or even depletion, the resulting estrous cycle disorders, decreased sex hormone secretion and decrease in or loss of fertility may indicate one or more pathological states and thus do not simulate the real pathophysiological condition of ovarian aging [8, 13].…”
Section: Introductionmentioning
confidence: 99%
“…We also observed herein that the FSH concentration in the serum of the mice was not affected by the LFD feeding for 3 weeks, suggesting that iron restriction for 3 weeks influences peripheral tissues (including the ovaries) but not the pituitary gland. In addition, since a previous study using Fshr gene target disruption mice showed reduced concentrations of LH [29] and progesterone [30] in the serum, we suspected that the LFD feeding also had an adverse effect on the ovulatory stage as was observed in the Fshr knockout mice, which may have resulted in a reduction of the oocyte's ability to develop to the blastocyst stage in this study.…”
Section: Discussionmentioning
confidence: 63%